The Concept of Museum Initiatives in the Lithuanian-Speaking Community in Early 20th Century - Leiputė, Rūta (Vilnius University Open Series, 2025)
The article examines the nature, goals, reflection, exhibit profiles and display decisions of the early 20th century museum initiatives in the Lithuanian-speaking communities in the Russian Empire, the United States of America, and the German Empire. It looks for similarities and differences between the initiatives, and examines the extent to which the initiatives approached the institutional level. The study highlights that museum initiatives were a relatively new, semi-professional phenomenon, they were mostly instrumentalized for the needs of the national movement, and that both public and individual engagement and collaboration were crucial.
Keywords: museum; nationalism; exhibition; exhibit; heritage conservation; institution